2016
DOI: 10.2323/jgam.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> cloning of large chromosomal segments into a BAC derivative by generalized transduction and recombineering in <i>Salmonella enterica</i>

Abstract: None of the authors of this manuscript has any financial or personal relationship with other people or organizations that could inappropriately influence their work. enzymes, which vary from insert to insert even for a given vector plasmid, and there is no need to purify and ligate DNA fragments, which is required in conventional recombinant techniques. This method, which relies on PCR amplification for the preparation of entire insert fragments (Bubeck et al., 1993;Jacobus and Gross, 2015;Li et al., 2011;Olin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The results showed that the ATCC 35953 strain could not be transformed by the relatively large plasmid DNAs pCF430 (10 kb) 33 and pAK1001 (8.4 kb) 34 , whereas i6 formed colonies, showing transformation efficiency at least four orders of magnitude higher than that of ATCC 35953 especially with pCF430 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 94%
“…The results showed that the ATCC 35953 strain could not be transformed by the relatively large plasmid DNAs pCF430 (10 kb) 33 and pAK1001 (8.4 kb) 34 , whereas i6 formed colonies, showing transformation efficiency at least four orders of magnitude higher than that of ATCC 35953 especially with pCF430 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 94%
“…Recombineering techniques that rely on λ Red recombinase and the FLP/FRT system have been used to construct large, precise clones (Kato, 2016) and precise gene fusions (Ellermeier et al, 2002). Here I extend these techniques to create a versatile, sitespecific, conjugation-mediated single-copy luciferase fusion system.…”
Section: Detection and Comparison Of Inducible Luminescence From Salm...mentioning
confidence: 99%